Fast computation of Fresnel diffraction field of a three-dimensional object for a pixelated optical device - (:unkn) unknown (OPTICAL SOC AMER, 2013)
In this paper, a fast algorithm is proposed for accurate calculation of the scalar optical diffraction on a pixelated optical device used in the reconstruction process from a three-dimensional object that is formed by scattered sample points over the space. In computer-generated holography, fast and accurate calculation of the diffraction field is an important and a challenging problem. Therefore, several fast algorithms can be found in the literature. The accuracy of the calculations can be determined by the signal processing techniques and the numerical methods used in the calculation of diffraction fields. Furthermore, the quality of reconstructed objects can be affected by the properties of optical devices employed in the reconstruction process. For instance, the pixelated structure of those devices has a significant effect on the reconstruction process. Therefore, the pixelated structure of the display device has to be taken into account. Furthermore, fast calculation of the diffraction pattern can be a bottleneck in dynamic holographic content generation. As a solution to the problems, we propose a fast and accurate algorithm based on a precomputed one-dimensional kernel and scaling of that kernel for the computation of the diffraction pattern for a pixelated display. (c) 2012 Optical Society of America
Keywords: COMPUTER-GENERATED HOLOGRAMS; LOOK-UP TABLE; SURFACE OBJECTS; RECONSTRUCTION; PROPAGATION; TRANSFORM; ALGORITHM; PLANES